Copula approach to select input/output variables for DEA - Olcay Alpay; Elvan Aktürk Hayat (An International Journal of Optimization and Control: Theories & Applications, 2016)
Determination of the input/output variables is an important issue in Data Envelopment Analysis (DEA). Researchers often refer to expert opinions in defining these variables. The purpose of this paper is to propose a new approach to determine the input/output variables, it is important to keep in mind that especially when there is no any priori information about variable selection. This new proposed technique is based on a theoretical method which is called “Copula”. Copula functions are used for modeling the dependency structure of the variables with each other. Also we use the local dependence function which analyzes the point dependency of variables of copulas to define the input/output variables. To illustrate the usefulness of the proposed approach, we conduct two applications using simulated and real data and compare the efficiencies in DEA. Our results show that new approach gives values close to perfection.